Pengaruh Profitabilitas, Exchange Rate, Inovasi Perusahaan dan Mekanisme Bonus terhadap Transfer Pricing Aggressiveness - Azmi Muzal; Hexana Sri Lastanti (Syntax Corporation Indonesia, 2024)
This study aims to see the effect of profitability, exchange rate, company innovation, and bonus mechanism on the aggressiveness of transfer pricing. The data and sampling used in this study are consumer sector companies, both primary and non-primary, listed on the Indonesia Stock Exchange in 2018-2022. The analysis method used is multiple linear regression analysis by utilizing the SPSS application. The results showed that simultaneously all independent variables have a significant influence on the dependent variable. However, partially, profitability and exchange rate have a positive effect on transfer pricing aggressiveness, while corporate innovation and bonus mechanism have no effect on transfer pricing aggressiveness.